Improving self-care for heart failure for seniors: the impact of video and written education and decision aids - Veroff, David R; Sullivan, Lisa A; Shoptaw, E J; Venator, Benjamin; Ochoa-Arvelo, Tamara; Baxter, Jonathan R; Manocchia, Michael; Wennberg, David (Population health management, 2012)
Heart failure poses a substantial burden on health care expenditures and quality of life; therefore, strategies to improve health behaviors for heart failure are essential. Highly effective medical decision aids can enable health improvements for people with heart failure. In this randomized controlled study, individuals with heart failure in a private Medicare plan were randomized into either an intervention or control group. Participants in the intervention group received basic program information and a simple fact sheet about heart failure, plus a medical decision aid, Living with Heart Failure DVD and booklet; patients randomized to the control group received the basic written materials only. The study was powered to detect a 5% difference in the primary outcome measure (daily weight monitoring). Participants were surveyed 4 weeks after outreach materials were mailed. There were 480 survey respondents: 246 in the intervention group; 234 in the control group. Intervention group respondents were significantly more likely to weigh themselves daily (P=0.05) than control group respondents (44% versus 38%). The intervention group was more likely than the control group to monitor fluid intake (47% versus 44%) and follow a low-sodium diet (83% versus 77%). Other health behavior differences were not statistically significant. The DVD decision aid increased levels of daily weight monitoring and other important health behaviors. Broad application of inexpensive behavior change interventions, such as a DVD/booklet program, should help to facilitate important, routine self-care behaviors for individuals with heart failure.